2014
DOI: 10.1111/jcmm.12316
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of isolated functional mitochondria: involvement of macropinocytosis

Abstract: In eukaryotic cells, mitochondrial dysfunction is associated with a variety of human diseases. Delivery of exogenous functional mitochondria into damaged cells has been proposed as a mechanism of cell transplant and physiological repair for damaged tissue. We here demonstrated that isolated mitochondria can be transferred into homogeneic and xenogeneic cells by simple co-incubation using genetically labelled mitochondria, and elucidated the mechanism and the effect of direct mitochondrial transfer. Intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
203
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(218 citation statements)
references
References 35 publications
12
203
0
3
Order By: Relevance
“…The mechanism(s) involved in transplantation of exogenous mitochondria into smooth muscle cells of pulmonary arteries may be more complicated in vivo than in vitro as reported recently from other lab [16] and ours [8]. In addition to the direct interaction between mitochondrial membrane and cytoplasma membrane and the subsequent processes like fusion and or endocytosis as suggested from recent works of another lab [16] and ours [8], the other possible pathways may be related with the interspace and gap junctional channels between endothelial and smooth muscle cells as well as those between smooth muscle cells, since mitochondrial transfer between cells was reported in very recent studies [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism(s) involved in transplantation of exogenous mitochondria into smooth muscle cells of pulmonary arteries may be more complicated in vivo than in vitro as reported recently from other lab [16] and ours [8]. In addition to the direct interaction between mitochondrial membrane and cytoplasma membrane and the subsequent processes like fusion and or endocytosis as suggested from recent works of another lab [16] and ours [8], the other possible pathways may be related with the interspace and gap junctional channels between endothelial and smooth muscle cells as well as those between smooth muscle cells, since mitochondrial transfer between cells was reported in very recent studies [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…A defined ratio of mixed donor mitochondria can also be simultaneously transferred into a cell, which aid in studies of heteroplasmy mtDNA competition, nuclear/mitochondrial genome compatibility, and kinetics of metabolic rewiring. Finally, the nanoblade could dissect mechanisms of inefficient, uncontrolled, and spontaneous cellular uptake of mitochondria without cell fusion (Katrangi et al, 2007; Kitani et al, 2014; Masuzawa et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the latter results, cellular uptake of mitochondria from the media was discovered to be temperature dependent, could occur between species, and was shown for MDA-MB-435, COLO 205, and MCF-7 cell lines (Katrangi et al, 2007). The incorporation of isolated mitochondria into endometrial gland-derived mesenchymal cells was also shown to be dose-dependent (Kitani et al, 2014a; Kitani et al, 2014b). Rho-zero (ρ0) cells can be generated that lack mtDNA and, therefore, cannot respire or generate ATP by OXPHOS and become uridine auxotrophs due to the inactivation of ETC-dependent dihydroorotate dehydrogenase (King and Attardi, 1989).…”
Section: Direct Uptake By Co-culture With Isolated Mitochondriamentioning
confidence: 99%
“…Rho-zero (ρ0) cells can be generated that lack mtDNA and, therefore, cannot respire or generate ATP by OXPHOS and become uridine auxotrophs due to the inactivation of ETC-dependent dihydroorotate dehydrogenase (King and Attardi, 1989). The uptake of isolated mitochondria into ρ0 cells increased cell viability and respiration (Kitani et al, 2014b). The uptake mechanism did not involve clathrin-mediated endocytosis, but data obtained using inhibitors against microtubule assembly, actin polymerization, and Na+/H+ exchange suggested that non-selective macropinocytosis was a key component (Kitani et al, 2014b).…”
Section: Direct Uptake By Co-culture With Isolated Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation